Environmental management begins in the family - Jesús Alfredo Liévanos Barrera; Isaias de la Rosa Gomez (Journal of Sustainability Perspectives, 2022)
The Institito Tecnológico de Toluca, is a higher level educational institution, which belongs to the National Technological System of Mexico, which has 9 degrees, in the engineering area, citing: Industrial (IE), Chemical (CI), Logistics (LE), Electromechanical (EE), bussines management’s (BME), Electronics (EE), Mechatronics (MI), Computational Systems (CSI) and Information and Communication Technologies (ICTE,) and 3 postgraduate degrees: Master of Engineering Sciences (MES), Master of Sciences in Environmental Engineering (MSEE) and Doctorate in Environmental Sciences (DES), with a population of 5,408 students. Being a proudly public institution and classified as the best, by its employers at the state level, within which there is a Coordination called Institutional Environmental Program (IEP), which manages various strategies for the care, protection, remediation of the environment. But, in Mexico, since March 2019, educational institutions have been closed due to the context of the pandemic caused by covid-19. Academic activity being carried out, since then to date, via virtual. Faced with such a complicated, difficult and uncertain scenario. An environmental management model was developed, so that students from their homes develop prevention programs, protection and care of the ecosystem, developing sustainable strategies. Starting from the premise: If there is a polluting society it is because there are families that pollute, the family is the mirror of what happens in society. Within this program, an amalgam of strategies was considered, starting with motivation, awareness, reflection, knowledge and self-management to detonate a new environmental culture, starting from their homes and extending it to their families and neighbors. To carry out a multiplier effect, in geometric progression, having an excellent response from the students of the Instituto Tecnológico de Toluca (ITT). Among the various strategies within an application scenario, the following are cited: Responsible-reflective consumption, no generation of unnecessary waste (organic food waste reduction), no use of Unicel (expanded polystyrene), use of single-use containers (elimination of PET), no oil disposal used from the kitchen (application of a collection program), induction to the modification of nutritional intake by substituting beef for chicken, fish and vegetables, separation and classification of garbage, application of the use of compost for the organic food remains, water saving and leak elimination program, collection of cigarette butts thrown in public roads and gardens. Turning off lights in homes when they are not necessary (energy saving), only use of a motor vehicle in very necessary cases (mitigation of the effects of climate change). With these actions that began in this year 2021, we consider that we are working towards the reduction of negative environmental impacts, detonating a new culture and environmental awareness, among higher-level students (undergraduate), having a participation and involvement of 1,700 families and a number that continues to grow. Additionally, we are contributing to the 2030 Agenda, of the Sustainable Development Goals (SDG), especially regarding the objectives: 4.- Quality education, 11.- Sustainable cities and communities and 13.- Actions for the climate.Keyword: family, environmental culture, awareness, virtual scene, pollutants